2019
DOI: 10.1186/s12883-019-1288-4
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanical study of gait initiation in Down syndrome

Abstract: Background Gait Initiation (GI) is a functional task that challenges the balance control requiring weight shift and a transition from standing to walking. Individuals with Down Syndrome (DS) walk with low velocity, prolonged stance and shorter steps beside an increased support base. However, no studies performed GI analysis on this population. The aim of this study is to quantitatively characterize the GI task in subjects with DS compared with a typically developed control group. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 29 publications
0
16
0
2
Order By: Relevance
“…The COP trajectories during APAs along the AP and ML axes are controlled by the "coordination" pattern between the ventrodorsal muscles (dominated by ankle muscles) and ML muscles (dominated by hip muscles) (Winter, 2009). Thus, the COP trajectory of APAs could detect the development of coordination patterns and direction specificities in APAs and may be an effective parameter (Corsi et al, 2019). To the best of our knowledge, only one study addresses the detailed COP trajectory during GI (Malouin & Richards, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The COP trajectories during APAs along the AP and ML axes are controlled by the "coordination" pattern between the ventrodorsal muscles (dominated by ankle muscles) and ML muscles (dominated by hip muscles) (Winter, 2009). Thus, the COP trajectory of APAs could detect the development of coordination patterns and direction specificities in APAs and may be an effective parameter (Corsi et al, 2019). To the best of our knowledge, only one study addresses the detailed COP trajectory during GI (Malouin & Richards, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Gait initiation is a functional task that is classically used in the literature as an experimental paradigm to investigate how the central nervous system (CNS) controls balance in dynamical conditions in both healthy adults [e.g., (31)(32)(33)(34)(35) for recent articles] and pathological patients [e.g., (36)(37)(38)(39)(40) for recent articles]. Gait initiation appears to be the major biomechanical model, complementary to the classical clinical test, in order to predict postural disorders in elderly fallers and non-fallers (41)(42)(43)(44).…”
Section: Introductionmentioning
confidence: 99%
“…Many researches have studied the manual dexterity of persons with Down syndrome and found that such persons suffered from difficulties in hand movement and control [ 40 ]. Despite such difficulties, it is possible to improve manual dexterity skills by constant training and by external support tools [ 41 ]. It has been found that training children on hands movement enhances children’s hands movement control [ 22 ].…”
Section: Discussionmentioning
confidence: 99%